Observation of B ->eta ' K-* and evidence for B+->eta ' p(+) - Aubert, B; Barate, R; Bona, M; Boutigny, D; Couderc, F; Karyotakis, Y; Lees, J; Poireau, V; Tisserand, V; Zghiche, A; Grauges, E; Palano, A; et al. (2007)
We present an observation of B→η′K*. The data sample corresponds to 232×106 BB̄ pairs collected with the BABAR detector at the PEP-II asymmetric-energy B factory at the Stanford Linear Accelerator Center. We measure the branching fractions (in units of 10-6) B(B0→η′K*0)=3.8±1.1±0.5 and B(B+→η′K*+)=4.9-1.7+1.9±0.8, where the first error is statistical and the second systematic. A simultaneous fit results in the observation of B→η′K* with B(B→η′K*)= 4.1-0.9+1.0±0.5. We also search for B→η′ρ and η′f0(980)(f0→π+π-) with results and 90% confidence level upper limits B(B+→η′ρ+)=8.7-2.8-1.3+3.1+2.3 (<14), B(B0→η′ρ0)<3.7, and B(B0→η′f0(980) (f0→π+π-))<1.5. Charge asymmetries in the channels with significant yields are consistent with zero. © 2007 The American Physical Society.